Digital Literacy Ecosystems in Higher Education: Strategies for Preparing Future Science Teachers for Global Disruption - Qothrunnada Qothrunnada; Baiq Nabila Saufika Zainuri (Indonesian Publication Center, 2026)
Rapid technological development requires higher education to prepare future science teachers with strong and adaptive digital literacy. However, digital literacy is often narrowly interpreted as technical skills, without considering its connection to the broader educational system. This article examines digital literacy in higher education from an ecosystem perspective as a strategy for preparing future science teachers to navigate global disruption. This study employs a systematic literature review of reputable scholarly articles addressing digital literacy, digital competence, and teacher education in higher education contexts. The findings indicate that digital literacy should be understood as an interconnected system involving individuals, learning experiences, institutional policies, and the use of technology in teaching and learning. The review also reveals considerable variation in students’ and pre-service teachers’ digital literacy levels, influenced by instructional design and institutional support. Well-planned and sustained integration of digital literacy supports the professional readiness of future science teachers to use technology critically and responsibly. The study concludes that an ecosystem-based approach is essential for strengthening digital literacy in science teacher education, enabling future teachers to respond effectively to ongoing global educational challenges.